Pengaruh Teknik Pemolesan Satu Langkah dan Beberapa Langkah Terhadap Kekasaran Permukaan Resin Komposit Nanofiller - Diana Setya Ningsih; Viona Diansari; Widyarti M (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
Composite resin restoration (nanofiller) should be smooth and glossy to improve aesthetic and prevent food retention. Therefore, polishing procedure is need to reduce surface roughness. Polishing technique in dentistry consist one step and multiple step polishing technique. The aim of this study was evaluated the effect of one step and multiple step polishing technique on surface roughness nanofiller composite resin Thirty specimens were restored with Z 350 (diameter 10 mm and thichness 3 mm). Specimens were divided into 3 groups (n=10): Unpolished, One step and multiple step. All specimens were mensured surface roughness using surface roughness tester Mitotuyu sjp 201. Data were analized using one way ANOVA and post hoc Duncan. The result of this study showed surface roughness of nanofiller composite resin was significantly difference between unpolish, one step and multiple step polishing system (p<0,005). As conclusion, surface roughness of multiple step polishing system is lower then one step and unpolished.